2013
DOI: 10.1593/tlo.13523
|View full text |Cite
|
Sign up to set email alerts
|

Cytosine 5-Hydroxymethylation of the LZTS1 Gene Is Reduced in Breast Cancer

Abstract: Change of DNA cytosine methylation (5mC) is an early event in the development of cancer, and the recent discovery of a 5-hydroxymethylated form (5hmC) of cytosine suggests a regulatory epigenetic role that might be different from 5-methylcytosine. Here, we aimed at elucidating the role of 5hmC in breast cancer. To interrogate the 5hmC levels of the leucine zipper, putative tumor suppressor 1 (LZTS1) gene in detail, we analyzed 75 primary breast cancer tissue samples from initial diagnosis and 12 normal breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Our recent work has indicated that vitamin C promotes 5hmC generation by serving as a cofactor for TETs 11 , 12 . Intracellular vitamin C deficiency would fail to maintain the catalytic activity of TETs, resulting in the loss of 5hmC as observed in breast cancer 3 6 . To identify potential factors responsible for the observed loss of 5hmC in primary human breast cancers, we analyzed RNA-seq data from The Cancer Genome Atlas (TCGA).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent work has indicated that vitamin C promotes 5hmC generation by serving as a cofactor for TETs 11 , 12 . Intracellular vitamin C deficiency would fail to maintain the catalytic activity of TETs, resulting in the loss of 5hmC as observed in breast cancer 3 6 . To identify potential factors responsible for the observed loss of 5hmC in primary human breast cancers, we analyzed RNA-seq data from The Cancer Genome Atlas (TCGA).…”
Section: Resultsmentioning
confidence: 99%
“…Global loss of 5-hydroxymethylcytosine (5hmC) has been recognized as an epigenetic hallmark in most, if not all, types of cancer including breast cancer 2 . 5hmC content is relatively high in normal breast epithelial cells, but shows a progressive loss in breast cancers 3 6 . 5hmC is converted from 5-methylcytosine (5mC) as an initial step of active DNA demethylation, which is catalyzed by ten-eleven translocation (TET) methylcytosine dioxygenases 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The majority of genes with 5hmC reduction had been shown to be downregulated in hepatocellular carcinoma, indicating 5hmc loss might be used to transcriptionally inactivate certain tumor suppressors since early studies had shown that 5hmC, especially those located in gene bodies, were associated with transcriptional activity. As an example, we checked the 5hmC levels of two tumor suppressors: LZTS1 in breast cancer and XPO4 in liver cancer [ 21 , 22 ]. By examining 75 primary breast cancers and 12 normal breast tissues, Wielscher et al had recently found that LZTS1 had significantly lower 5hmC content in tumors compared to normal breast tissues in the region between the 5′UTR to the second exon while no significant differences were observed for 5mC.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies that have identified such loci describe the basis of 5hmC mediated gene regulation and also identify potential and novel regions that can be involved in regulation across the genome. Loss of 5hmC has been observed in Homeobox A Cluster (HOXA) genes, mir-200 and Leucine Zipper Tumor Suppressor 1 (LZTS1), leading to hypermethylation in those regions and promoting breast tumor progression and metastasis and in contrast, 5hmC gain at regions of (Tumor Necrosis Factor-Alpha) TNFA enable cell survival and stemness in breast tumor initiating cells (BTICs) under hypoxia [40][41][42][43]. Superoxide Dismutase 3 (SOD3), which is frequently downregulated in squamous cell carcinomas and adenocarcinomas, is also less expressed in lung (A549), breast (ZR75-1) and prostate (PC3) cancer cell lines as it incurs loss of 5hmC at its promoter region [44].…”
Section: Interplay Between 5-hydroxymethylcytosine and Cancermentioning
confidence: 99%